Impact of Behavioral, Psychological and Social Dimensions upon Juvenile Delinquency - hamoo, Siham; hossien, hassan (Iraqi National Journal of Nursing Specialties, 2014)
Objective: The present study aims at identifying the dimensions behind juvenile delinquency, and to identify their socio-demographic characteristics of gender, age, and type of delinquency. Methodology: A descriptive study was conducted in correctional schools in Baghdad City to identify the behavioral, psychological, and social dimensions contributed to juvenile delinquency. The study sample consisted of (50) juvenile delinquents, of them, 27 males, and 23 females whose ages range from (12 - 20) years. Those delinquents live in males’ correctional school in Al-Shalichia, and females’ correctional school in Al-Karradah, in Baghdad City. The study sample was selected in purposively. The study questionnaire was designed by researchers in order to achieve the study aims. The questionnaire consisted of four parts; delinquents’ socio-demographic characteristics, their behavioral factors, their psychological factors, and their social factors. This questionnaire consisted of (61) items. Its reliability was determined through a pilot study. Data were collected by using this questionnaire for the period from 10/02/2013 through 17/02/2013. Data were analyzed by using descriptive statistical measures of frequency, percentage, and mean. Results: The study results demonstrated that the vast majority of juvenile delinquents are aged 15-17 years, and males were at the age of 14-16 years when they committed the delinquency, most juvenile delinquents were of those who had unable to read and write, the vast majority of delinquents live with their parents. Recommendations: The study recommends to engage each of family, school, and social and psychological agencies in delinquents’ rehabilitation and their integration into the society, there should be a cooperation with the mass media to enlighten all segments of the society about the seriousness and prevalence of juvenile delinquency, its causes and ways to prevent them, updating legislations and rules related juveniles in a way consists with international standards of juveniles’ rights, as delineated by the instructional principles of the United Nations in order to prevent juveniles’ delinquency